Ultra-high curvature sensors for multi-bend structures using fiber Bragg gratings - Jang, Minsu; Kim, Jun Sik; Um, Soong Ho; Yang, Sungwook; Kim, Jinseok (OPTICAL SOC AMER, 2019)
Measuring high curvatures is essential in various applications such as structural engineering, medical treatment, and robotics. Herein, we present a novel ultra-high curvature sensor with an ultra-thin and highly flexible structure incorporating fiber Bragg gratings (FBGs). The sensor can measure curvature of bidirectional bending up to 200 m(-1). In addition, the multi-bend curvature sensor in conjunction with the proposed calibration scheme enables the accurate reconstruction of a curve with varying curvature. The sensitivity and the accuracy of the curvature sensor are investigated for different sensor designs. Finally, we demonstrate the accurate shape sensing of various 2-D patterns using the multi-bend curvatures sensor. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement